2020
DOI: 10.1007/s11368-020-02762-5
|View full text |Cite|
|
Sign up to set email alerts
|

Water dynamics at the urban soil-atmosphere interface—rainwater storage in paved surfaces and its dependence on rain event characteristics

Abstract: Purpose The surface store governs the rainwater partition, e.g., water storage and evaporation on paved surfaces, especially for low-intensity and low-sum rain events, which account for the greatest part of the total rainfall in a temperate climate city like Berlin, Germany. The surface store S is a fixed value, dependent on surface relief and pore system characteristics. Contrary, in this study, the surface storage was assumed to depend also on the rain intensity, thus being variable from event to event. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Note, that the static RC concept used in this study has not been developed to analyze water availabilities, but for maximum runoff prediction, thus allowing possible overestimation. Otherwise, an improved rainfall run-off model, using single rainfall events would need to be applied [137]. Generally, eRO < 1 indicates that only a part of the RO can be evaporated by the VGSa surplus of RO-regarding a fully greened facade and sufficient water supply of the plants.…”
Section: Run-off Reduction Potentialsmentioning
confidence: 99%
“…Note, that the static RC concept used in this study has not been developed to analyze water availabilities, but for maximum runoff prediction, thus allowing possible overestimation. Otherwise, an improved rainfall run-off model, using single rainfall events would need to be applied [137]. Generally, eRO < 1 indicates that only a part of the RO can be evaporated by the VGSa surplus of RO-regarding a fully greened facade and sufficient water supply of the plants.…”
Section: Run-off Reduction Potentialsmentioning
confidence: 99%
“…The surface material, the use of the surface and the rainfall distribution influences the initial abstraction and the quality of the collected run-off. The initial abstraction is the rainfall stored on the run-off surface and is subsequently evaporated [56][57][58].…”
Section: Sub-module 2: Hydraulicmentioning
confidence: 99%
“…The use of a constant RC is widespread in RWH calculation. However, recent studies have questioned this approach as results have shown a dependency of RC on rainfall intensity [58].…”
Section: Sub-module 2: Hydraulicmentioning
confidence: 99%
“…In partly sealed soils, the paving material itself plays the main role in the hydrological balance. The existence of depressions leads to ponding and creates suitable conditions for evaporation [11][12][13][14], whereas cracks and slopes alter flow regimes and runoff generation, respectively [15,16]. Moreover, the construction of the pavers also plays a significant role in the evaporation rate.…”
Section: Introductionmentioning
confidence: 99%